Geochronological constraints on the age of a Permo–Triassic impact event: U–Pb and 40Ar/39Ar results for the 40 km Araguainha structure of central Brazil - Tohver, E; Lana, C; Cawood, Peter; Fletcher, Ian; Jourdan, Fred; Sherlock, Sarah; Rasmussen, Birger; Trindade, R; Yokoyama, E; Souza-Filho, C; Marangoni, Y (Pergamon-Elsevier Science Ltd, 2012)
Impact cratering has been a fundamental geological process in Earth history with major ramifications for the biosphere. The complexity of shocked and melted rocks within impact structures presents difficulties for accurate and precise radiogenic isotope age determination, hampering the assessment of the effects of an individual event in the geological record. We demonstrate the utility of a multi-chronometer approach in our study of samples from the 40 km diameter Araguainha impact structure of central Brazil. Samples of uplifted basement granite display abundant evidence of shock deformation, but U/Pb ages of shocked zircons and the 40Ar/39Ar ages of feldspar from the granite largely preserve the igneous crystallization and cooling history. Mixed results are obtained from in situ 40Ar/39Ar spot analyses of shocked igneous biotites in the granite, with deformation along kink-bands resulting in highly localized, partial resetting in these grains. Likewise, spot analyses of perlitic glass from pseudotachylitic breccia samples reflect a combination of argon inheritance from wall rock material, the age of the glass itself, and post-impact devitrification. The timing of crater formation is better assessed using samples of impact generated melt rock where isotopic resetting is associated with textural evidence of melting and in situ crystallization.Granular aggregates of neocrystallized zircon form a cluster of ten U–Pb ages that yield a “Concordia” age of 247.8 ± 3.8 Ma. The possibility of Pb loss from this population suggests that this is a minimum age for the impact event. The best evidence for the age of the impact comes from the U–Th–Pb dating of neocrystallized monazite and 40Ar/39Ar step heating of three separate populations of post-impact, inclusion-rich quartz grains that are derived from the infill of miarolitic cavities. The 206Pb/238U age of 254.5 ± 3.2 Ma (2sigma error) and 208Pb/232Th age of 255.2 ± 4.8 Ma (2sigma error) of monazite, together with the inverse, 18 point isochron age of 254 ± 10Ma (MSWD = 0.52) for the inclusion-rich quartz grains yield a weighted mean age of 254.7 ± 2.5 Ma (0.99%, 2r error) for the impact event. The age of the Araguainha crater overlaps with the timing of the Permo–Triassic boundary, within error, but the calculated energy released by the Araguainha impact is insufficient to be a direct cause of the global mass extinction. However, the regional effects of the Araguainha impact event in the Parana–Karoo Basin may have been substantial.